2014
DOI: 10.1590/s0100-736x2014001200006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência, distribuição espacial e fatores de risco para cisticercose bovina no estado de São Paulo

Abstract: O presente trabalho teve como objetivos determinar a prevalência, a distribuição geográfica bem como os fatores e áreas de risco associados à cisticercose bovina no Estado de São Paulo. Foram inspecionados 34.443 animais, machos e fêmeas e com faixas etárias variando entre 18 a 60 meses. Os bovinos eram procedentes de 97 municípios do Estado de São Paulo, devidamente identificados e abatidos no período de outubro de 2010 a agosto de 2011, em um frigorífico localizado na cidade de Ipuã-SP, sob supervisão do SIF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
2
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 9 publications
0
7
2
5
Order By: Relevance
“…The prevalence value assessed in this study (0·53%) is lower than the value reported in Brazil (1·05%) (Dutra et al 2012), and in the states of Paraná (2·2%) (Guimarães-Peixoto et al 2012) and São Paulo (4·8%) (Ferreira et al 2014). In the other hand, the prevalence is similar to the value reported in the state of Mato Grosso (0·08%) (Rossi et al 2016), which is located in the same Brazilian region (West-Centre).…”
Section: Discussioncontrasting
confidence: 66%
“…The prevalence value assessed in this study (0·53%) is lower than the value reported in Brazil (1·05%) (Dutra et al 2012), and in the states of Paraná (2·2%) (Guimarães-Peixoto et al 2012) and São Paulo (4·8%) (Ferreira et al 2014). In the other hand, the prevalence is similar to the value reported in the state of Mato Grosso (0·08%) (Rossi et al 2016), which is located in the same Brazilian region (West-Centre).…”
Section: Discussioncontrasting
confidence: 66%
“…After fasting for 12 h, cattle were slaughtered after stunning with a bolt gun, as commonly done in the meat industry. Inspection work on the slaughter lines was carried out by a team of inspection agents duly trained to carry out the post-mortem inspection under the supervision and responsibility of an official veterinary doctor of the Federal Inspection Service, as described by Ferreira et al (2014).…”
Section: Methodsmentioning
confidence: 99%
“…Carcasses with lesions that indicated cysticerci were sent to the Department of Final Inspection for parasite detection as described by Ferreira et al (2014).…”
Section: Methodsmentioning
confidence: 99%
“…Bovine cysticercosis caused by Taenia saginata is an important cattle disease, causing economic losses to the meat production chain due to the condemnation and downgrading of infected carcasses [4]. Furthermore, this cestode causing taeniasis in humans is a health issue, especially in regions with poor sanitary conditions, associated with socioeconomic and cultural aspects as the consumption of undercooked or raw beef [5,6]. Humans are infected by ingestion of viable T. saginata cysts in meat, the adult worm develops in the small intestine and releases gravid proglottids full of eggs in the feces contaminating the environment in areas with no sewage treatment.…”
Section: Introductionmentioning
confidence: 99%